In vivo anti-hyperlipidemic activity of the triterpene from the stem bark of Protorhus longifolia (Benrh) Engl - Machaba, Kgothatso E (Lipids Health Dis, 2014)
BACKGROUND: Hyperlipidemia, a metabolic disorder of lipids, is a well known risk factor of cardiovascular events and metabolic syndrome. In this study, the in vivo lipid-lowering activity of the triterpene (Methyl-3β-hydroxylanosta-9,24-dien-21-oate), isolated from the stem bark of Protorhus longifolia, in high fat diet (HFD)-induced hyperlipidemic rats was investigated. METHODS: Structure of the isolated compound was established and confirmed based on spectral (NMR, HRMS, IR) data analysis. Rats were divided into two groups; normal group (fed the normal commercial rats’ chow) and the HFD group. After 21 days of experimental period on their respective diets, the HFD rats were sub-divided into 4 groups of six rats per group. Two of the HFD groups were orally treated with the triterpene (100 and 200 mg/kg body weight) for 15 days. At the end of the experimental periods, the rats were sacrificed and blood samples were collected for biochemical assays. RESULTS: The results show that there were significant increases in total serum cholesterol (TC, 15.72 mmol/L) and low-density lipoprotein cholesterol (LDL-c, 7.41 mmol/L) with a reduction in high-density lipoprotein cholesterol (HDL-c, 14.75 mmol/L) in HFD-induced hyperlipidemic rats after 21 days. Oral administration of the triterpene (100 mg/kg.bw and 200 mg/kg.bw) for a period of 15 days resulted in significant lowering of the levels of TC (7.51 mmol/L) and LDL-c (4.46 mmol/L) with an increase in HDL-c (47.3 mmol/L) in HFD-induced hyperlipidemic rats. Significant decrease in atherogenic index and coronary risk index by the triterpene was observed in HFD-induced hyperlipidemic rats. CONCLUSIONS: The triterpene could effectively reduce or control the amount of serum cholesterol and LDL. It is apparent that the compound could contribute to new formulation with significant hypolipidemic effects. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/1476-511X-13-131) contains supplementary material, which is available to authorized users.